Gluteal Compartment Syndrome Following Abdominal Aortic Aneurysm Treatment: Case Report and Review of the Literature. (December 2016) - Viviani, Emanuela; Giribono, Anna Maria; Narese, Donatella; Ferrara, Doriana; Servillo, Giuseppe; del Guercio, Luca; Bracale, Umberto Marcello
Compartment syndrome (CS) is a pathological increase of the interstitial pressure within the closed osseous fascial compartments. Trauma is the most common cause, followed by embolization, burns, and iatrogenic injuries; it usually involves the limbs. The major issue when dealing with CS is the possibility to do an early diagnosis in order to intervene precociously, through a fasciotomy, reducing the risk of tissue, vascular and nervous damage. Although it is an infrequent condition, it is potentially life threatening. In our case report, we present a 59-year-old patient, smoker, affected by hypertension, dyslipidemia, chronic renal failure, and morbid obesity who came at our attention for a 6-cm abdominal aorta aneurysm, treated with an aorto-aortic graft. Within 24 hours from surgery, the patient presented acute ischemia of the right lower limb due to thrombosis of the common iliac artery and underwent the positioning of a kissing stent at the aortic bifurcation. In the immediate postoperative period, a relevant increase in serum creatinine, creatine phosphokinase, and myoglobin value was recorded, associated with clinical presentation of swelling in the right buttock with intense pain. The diagnosis of gluteal CS was confirmed by the measurement of the gluteal compartment pressure, which resulted of 110 mm Hg. The treatment of the CS consisted in gluteal dermofasciotomy, surgical debridement of the buttock, and positioning of negative pressure medication, associated with infusive therapy, avoiding hemodialysis. Because of the epidural anesthesia only later on it was possible to observe a persistent plegia of the right lower limb, which was solved within 1 month of neurological and physical therapy. With our experience, we can state that the CS is an extremely severe complication that can occur in vascular surgeries and it should therefore be kept in mind in the short-term postoperative period in order to guarantee a precocious diagnosis and immediate treatment.